Community survey data of permafrost thaw, coastal erosion, and civil infrastructure damage in Point Lay, Wainwright, Utqiaġvik, and Kaktovik, Alaska. 29 October 2021 – 1 February 2022. - Min Liew; Ming Xiao; Louise Farquharson; Dmitry Nicolsky; Anne Jensen; Vladimir Romanovsky; Jana Peirce; Lilian Alessa; Christopher McComb; Xiong Zhang; Benjamin Jones (Arctic Data Center, 2022)
This dataset presents the results of a community survey that was designed to better understand the effects of permafrost degradation and coastal erosion on civil infrastructure. Observations were collected from residents in four Arctic coastal communities: Point Lay, Wainwright, Utqiaġvik, and Kaktovik. There are three categories of questions in this survey: permafrost degradation, coastal erosion, and infrastructure damage and repair. The participants identified changes in ground surface manifested by permafrost degradation in and around their communities. The options provided in the questionnaire included surface water ponding, sinkholes, ground surface collapse, differential ground settlement along roads and gravel pads, and others. The periods during which these changes have been happening were also recorded; the options include less than 6 months, 0.5–1 year, 1–3 years, 3–5 years, 5–10 years, and greater than 10 years. Participants also indicated the infrastructure types affected by permafrost degradation. The options include houses, runways, schools, ice cellars, water and sewer lines, and others. Effects of permafrost degradation on residential buildings, buried pipelines, utilidors, and roads were reported in the survey. Detailed information such as damage type, damage location, repair method, and effectiveness of repair methods was also recorded. For the questions related to coastal erosion, participants identified events of coastal erosion, periods during which coastal erosion has been happening, types of civil infrastructure affected, and types of erosion control measures implemented and their effectiveness. Participants were able to provide their plans if permafrost degradation and coastal erosion continue to happen. They identified the locations of permafrost degradation and coastal erosion on provided maps with three different scales of approximately 600 km, 40 km, and 8 km.